Adoptive cell therapy for cancer: combination strategies and biomarkers - Liu, Shiyu; Jiang, Weibo; Sheng, Jiyao; Wang, Lixuan; Cui, Mengying (Frontiers in Immunology, 2025)
Adoptive cell therapy (ACT) is a therapeutic approach that involves the isolation, modification, and expansion of immune cells ex vivo, followed by their reinfusion into the patient to enhance anti-tumor immune responses. Various forms of ACT have demonstrated promising clinical outcomes across multiple types of cancer. For example, chimeric antigen receptor (CAR)-T cell therapy, tumor-infiltrating lymphocyte (TIL) therapy, and T-cell receptor-engineered T cell (TCR-T) therapy have received approval from the US Food and Drug Administration. However, the clinical application of ACT remains constrained by limited efficacy and potentially life-threatening toxicities. Diminished efficacy may result from an immunosuppressive tumor microenvironment, poor trafficking and infiltration, exhaustion of infused cells, tumor heterogeneity, and antigen escape. To address these challenges, combination strategies have been developed with the goals of enhancing efficacy and managing adverse effects. Conventional treatments and non-ACT forms of immunotherapy have been incorporated into these combination approaches. Biomarkers play an essential role in optimizing ACT strategies and addressing associated complexities. They can aid in candidate selection, assess the quality of ACT products, monitor long-term therapeutic efficacy, manage toxicity, and guide combination regimens. This review briefly outlines six ACT modalities and their common limitations, summarizes current combination strategies, explores potential future regimens, and offers an overview of biomarkers relevant to ACT. These insights provide valuable guidance for the development and clinical implementation of more effective ACT-based therapies, ultimately aiming to improve patient outcomes.